Science Up in Smoke: One Psychiatrist’s Journey Through the Politics of Cannabis Legalization - Rettew, David C. (Adolescent Psychiatry, 2021)
Background: Many states are currently considering legislature that would legalize and commercialize cannabis for medical and recreational purposes. Physicians and other health professionals are frequently called upon to offer an expert opinion on the public health implications of these bills. For many, the role of a scientific expert and advocate in a political process is new. Objective: This study aims to outline themes and lessons learned for clinicians engaged in deliberations over cannabis legislation and to describe how science can get used and misused in the political process. Method: This article describes the experience of a psychiatrist who was actively involved in one state’s deliberations through cannabis legalization bills. Results: Major themes that emerged during the process are described as are recommendations for other health professionals who may find themselves involved in similar processes related to cannabis legalization and other controversial initiatives that rely on the interpretation of scientific information. Conclusion: Psychiatrists and other clinicians can make important contributions to the political process for legislative debates that involve science-based mental health information.
Keywords: legalization